Effects of metformin on body weight in patients with type 2 diabetes mellitus,receiving insulin analogue treatment - Tatiana Ivanovna Romantsova; T Sh Dzhavakhishvili; O V Roik (Сахарный диабет, 2013)
Aims. To study the dynamics of body weight, waist circumference, blood lipid and insulin demand in patients with type 2 diabetes mellitus (T2DM) during first year of combined treatment with metformin and insulin analogues, compared with insulin analogue monotherapy. Materials and Methods. We examined 78 patients with T2DM on newly initiated insulin therapy, including 54 females and 24 males. Median age was 56 [51.0; 64.0] years, median disease duration ? 9 [6.8;14.0] years. Participants were subdivided in two groups. First group was comprised of 48 subjects (33 females and 15 males), who received monotherapy with insulin analogues (glargine, de- temir, biphasic Aspart 30 and Humalog Mix 25 or rapid-acting lispro and aspart). Second group included 30 patients (18 females and12 males), who were treated with combined therapy (insulin analogues plus metformin). We measured HbA1c, plasma lipid composition, BMI, waist circumference and insulin demand initially and after one year of follow-up. Results. We showed that combined therapy vs. insulin monotherapy allows better glycemic compensation while reducing insulin demand and lowering risks for weight gain. Conclusions. Combined insulin analogue plus metformin treatment delivers better metabolic control in patients with T2DM and is as- sociated with lower risks for body weight gain and increase in insulin demand against monotherapy with insulin analogues.